2020
DOI: 10.21203/rs.2.14089/v5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Knowledge, Attitude and Practice towards rabies and associated factors among household heads in Mekelle city, Ethiopia

Abstract: Background: Rabies has a worldwide distribution in continental regions of Africa, Asia and the Latin America. Globally, the case fatality rate is 100% once a clinical sign is developed. Poor public awareness towards rabies is one of the major obstacles in any prevention and control scheme of the diseases. The study aimed to assess knowledge, attitude and practice (KAP) about rabies and associated factors among household heads in Mekelle city, Northern Ethiopia, 2016. Methods: A community based cross-sectional … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…However, the success of the adopted measures is largely contingent upon the level of knowledge, attitudes, and practices possessed by the inhabitants (Tachfouti et al, 2012;Zhong et al, 2020; Ajilore, Atakiti, & Onyenankeya, 2017). It is noted that studies related to knowledge, attitude, and practices are a common method to increase the knowledge base of the people which might result in positive changes in attitudes and practices leading to minimization of negative consequences (Sambo et al, 2014;Hagos et al, 2020). Prior empirical evidence suggested that panic emotion resulting from epidemics like SARS in 2003 was significantly associated with the level of knowledge and attitudes toward it and this issue posed difficulties in combating the outbreak of SARS (Tao, 2003;Person, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, the success of the adopted measures is largely contingent upon the level of knowledge, attitudes, and practices possessed by the inhabitants (Tachfouti et al, 2012;Zhong et al, 2020; Ajilore, Atakiti, & Onyenankeya, 2017). It is noted that studies related to knowledge, attitude, and practices are a common method to increase the knowledge base of the people which might result in positive changes in attitudes and practices leading to minimization of negative consequences (Sambo et al, 2014;Hagos et al, 2020). Prior empirical evidence suggested that panic emotion resulting from epidemics like SARS in 2003 was significantly associated with the level of knowledge and attitudes toward it and this issue posed difficulties in combating the outbreak of SARS (Tao, 2003;Person, 2004).…”
Section: Introductionmentioning
confidence: 99%